Early and Mid-Term Outcomes of Pulsed Field Ablation in Patients with Atrial Fibrillation - Olexandr V. Doronin; Maryna S. Meshkova (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. Pulsed field ablation (PFA) is emerging as a safe and effective non-thermal approach for catheter-based treatment of atrial fibrillation (AF). It selectively targets cardiac tissue while reducing the risk of collateral damage. In Ukraine, this technology was introduced in 2024.Aim. To evaluate the early and mid-term outcomes of PFA in patients with different forms of AF treated at a single Ukrainian center.Materials and Methods. A total of 48 patients underwent PFA between March 2024 and February 2025 using the FARAPULSE™ catheter. Remote follow-up data were obtained for 42 patients (33 with paroxysmal AF and 9 with persistent AF). All procedures were performed under general anesthesia following a standardized ablation protocol. For persistent AF, additional posterior wall isolation was performed. Key procedural metrics and rhythm outcomes were documented.Results. The mean follow-up duration was 6.6 ± 3.4 months. Sinus rhythm was maintained in 78.7 % of patients with paroxysmal AF and in 66.7 % of those with persistent AF. Among the latter, 67.1 % continued antiarrhythmic therapy. No procedural complications were reported. Overall symptomatic improvement was noted in 81.0 % of patients. The efficacy rate aligns with international multicenter trials, such as PULSED-AF and INSPIRE.Conclusions. Initial experience with pulsed field ablation in Ukraine demonstrates promising results for both paroxysmal and persistent AF. The procedure proved to be safe and effective, even during the operator’s learning curve. Continued research with extended follow-up and larger cohorts is warranted to validate long-term efficacy.